Enhancing EFL/ESL instruction through gamification: a comprehensive review of empirical evidence - Chan, Sumie; Lo, Noble (Frontiers in Education, 2024)
In the landscape of English language education, the integration of gamification has marked a transformative trend. This systematic review, utilizing a rapid evidence assessment methodology, critically examines thirty empirical studies from the Web of Science, spanning the years 2010 to 2022. It aims to synthesize the current body of research on the incorporation of gamification into EFL/ESL pedagogy. Our analysis reveals an ascending trajectory in the prevalence of gamification within this academic sphere and corroborates its efficacy as a catalyst for language acquisition. The collected evidence underscores gamification's role in enhancing English proficiency, influencing learners' attitudes and emotional engagement positively, and fostering an immersive language learning milieu. Furthermore, this review delineates strategic insights and identifies key gamification components instrumental in orchestrating gamified educational experiences. The implications of the findings extend to pedagogical practices, providing a guide for educators in the design and implementation of gamified language learning environments.